A Literature Review on Resource-Efficient Web Browsing in Low-End Mobile Computing Environments - Karin, Juliana (Universitas Komputer Indonesia, 2025)
The proliferation of mobile computing has bridged the digital divide, yet a significant portion of the global population relies on low-end mobile devices characterized by limited CPU power, RAM, and battery life. This paper provides a comprehensive literature review on resource-efficient web browsing strategies tailored for these constrained environments. As web applications become increasingly complex with heavy JavaScript frameworks and high-resolution media, the performance gap between high-end and low-end devices widens. We analyze current optimization techniques, including cloud-assisted browsing, code offloading, and lightweight browser architectures. The review identifies critical bottlenecks in memory management and energy consumption that current solutions struggle to address. By synthesizing recent research, this paper outlines the shift toward